The rhetoric of the body from Ovid to Shakespeare - Enterline, Lynn, 1956- (Cambridge studies in Renaissance literature and culture ;, 2000)
This persuasive book describes the complex, often violent connections between body and voice in Ovid's Metamorphoses and works by Petrarch, Marston and Shakespeare. Lynn Enterline brilliantly reveals how Ovid's stories of violence and desire disturb Renaissance conceptions of authorship and what makes the difference between male and female experience.